Identifikasi Penguasaan Konsep Matematika Dalam Penyelesaian Soal Kesetimbangan Kimia - Filzah Nasyanovariani, Dinda; Sahputra, Rachmad; Rustam, Rustam (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to identify students' mastery of mathematical concepts in solving chemical equilibrium problems. The type of research used is descriptive qualitative research. The research subjects were students of Class XI IPA 2 SMA Muhammadiyah 1 Pontianak who had taken high school chemistry subjects in Class XI. Data collection was done through written tests, interviews, and documentation. The results showed that students had not fully mastered the mathematical concepts needed in solving chemical equilibrium problems. Some mathematical concepts that have not been well mastered include algebraic operations, equations, and graphs. Students' biggest difficulty is in converting the information given in the problem into a mathematical model. This finding indicates the need to strengthen students' understanding of mathematical concepts, especially those related to the concepts needed in studying chemical equilibrium. In addition, better integration between mathematics learning and chemistry learning is needed so that students can apply mathematical concepts more effectively in solving chemical problems.